2017
DOI: 10.5964/jnc.v3i2.67
|View full text |Cite
|
Sign up to set email alerts
|

Operational momentum during ordering operations for size and number in 4-month-old infants

Abstract: An Operational Momentum (OM) effect is shown by 9-month-old infants during non-symbolic arithmetic, whereby they overestimate the outcomes to addition problems, and underestimate the outcomes to subtraction problems. Recent evidence has shown that this effect extends to ordering operations for size-based sequences in 12-month-olds. Here we provide evidence that OM occurs for ordering operations involving numerical sequences containing multiple quantity cues, but not size-based sequences, already at 4 months of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…Given the constraints of such a young population (with children as young as 37 months of age), the adoption of a between-subjects design would have proved necessary to include a descending operation, as they lose interest in the task rather quickly. However, the infants tested in Macchi Cassia et al (2017) showed an underestimation tendency after habituation to descending numerical sequences which was not dissimilar from the overestimation tendency they showed after habituation to ascending sequences. Therefore, testing for the generalizability of the obtained findings to descending ordering operations in young children would be worth further investigation.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…Given the constraints of such a young population (with children as young as 37 months of age), the adoption of a between-subjects design would have proved necessary to include a descending operation, as they lose interest in the task rather quickly. However, the infants tested in Macchi Cassia et al (2017) showed an underestimation tendency after habituation to descending numerical sequences which was not dissimilar from the overestimation tendency they showed after habituation to ascending sequences. Therefore, testing for the generalizability of the obtained findings to descending ordering operations in young children would be worth further investigation.…”
Section: Discussionmentioning
confidence: 47%
“…It is possible that there were indeed miscalculations arising from spatial shifts in the preschoolers, similar to the infants, but the study's design dampened them for the preschoolers. For instance, in the infant study (Macchi Cassia et al, 2017), an infant-controlled habituation procedure was employed, which gave each single participant ample time to encode and form a robust representation of the ordering operation. Moreover, during habituation infants were given multiple examples of the same ordering rule.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only few studies have tested OM in children, For instance, Macchi Cassia, McCrink, de Hevia, Gariboldi, and Bulf (2016), Macchi Cassia, Bulf, McCrink, and de Hevia (2017) found that just 4-monthold infants expected larger numerosities at a given position in the sequence when previously habituated to increasing numerical sequences but expected smaller numerosities when habituated to decreasing sequences. Knops, Zitzmann, and McCrink (2013) and…”
Section: Studies On Om In Childrenmentioning
confidence: 99%